Akt założycielski polskiego strukturalizmu immanentnego: Juliusza Kleinera Treść i forma w poezji - Obremski, Krzysztof (Przestrzenie Teorii, 2021)
In Polish literary studies methodology, Kleiner’s status as entirely marginal, if not anachronistic, can be justified only on one condition, namely if we overlook the study Content and form in poetry (“Przegląd Warszawski” 1922, r. 2, vol. 2, pp. 323–333), for it can be read as the rejected cornerstone of Polish immanent structuralism. Due to the ambiguity of the term “structuralism”, it is necessary to define its meaning here: it will be determined by the historical context, i.e. the Course in General Linguistics (first edition: 1916). Adopting Janusz Sławiński’s terminology, we may add that it is a rejected cornerstone of immanent (“unconscious”) structuralism not a formulated one.